What Ever Happened to the Worldwide Church of God? - Melton, J. Gordon (The journal of CESNUR, 2023)
Prominently cited as a "cult" by Christian counter-cult watchers in the twentieth century, the Worldwide Church of God (WCoG) experienced a downward trajectory beginning in the 1980s, massive schism in the 1990s, and then disappeared altogether early in the new century. Although no church named "Worldwide Church of God" continues to exist, the former WCoG maintains a significant presence both through its official continuing body, now renamed Grace Communion International, after having renounced most of its unique doctrinal heritage, but most substantively in four schismatic churches - the Philadelphia Church of God, the Living Church of God, the United Church of God, and the Restored Church of God - each of which has tried with some success to reproduce the former WCoG's beliefs and practices. Simultaneously, the WCoG and its present successors remain important reference points in ongoing discussions of both the nature of charisma and the process of schism in new religious movements. (A previous version of this paper was presented at the annual meeting of CESNUR in Vilnius, Lithuania, June 20-23, 2023).